Smartphones: reading habits and overuse. A qualitative study in Denmark, Lithuania and Spain - Levratto, Valeria; Suminas, Andrius; Schilhab, Theresa; Esbensen, Gertrud (Educación XX1, 2021)
Recently, the smartphone has become the key device in families and workplaces, changing people’s habits and ways of interaction in our liquid and hyperconnected societies. Little research has been done on the use of smartphones for reading, since the telephone was not associated with reading until very recently. This paper presents an overview of digital mobile reading in the digital literacy context and tries to answer different research questions, such as: how do people read on the smartphone? Do people have an addiction to/misuse of mobiles? Its objective is to offer empirical data about people’s experiences of digital mobile reading and to analyse how we depend on our smartphone through a small-scale qualitative study including different informants from three European capital cities: Copenhagen (Denmark), Madrid (Spain) and Vilnius (Lithuania). The paper does not aim to generalise its findings, but to advance the field of digital literacy research, a field in which the meaning (the interviews) has been interpreted in relation to a wider socio-cultural context. The results report that the “context”, the “time” and the “situation” where reading is carried out are decisive for understanding; furthermore, the type of navigation that readers can perform on the smartphone has important consequences in the reading process, hence, the layout must be well designed for active and attentive users on mobile devices. Our Informants assert that situations like boredom, waiting or loneliness can induce the use of the smartphone. Therefore, more research is needed, in different areas and with new digital literacy programmes in order to help young people (and adults) use their mobiles as advantageously as possible.